Potential moderators of the effects of blood flow restriction training on muscle strength and hypertrophy: A meta-analysis based on a comparison with high-load resistance training - Geng, Y.; Wu, X.; Zhang, Y.; Zhang, M. (Sports Medicine - Open, 2024)
Background While it has been examined whether there are similar magnitudes of muscle strength and hypertrophy adaptations between low-load resistance training combined with blood-flow restriction training (BFR-RT) and high-load resistance training (HL-RT), some important potential moderators (e.g., age, sex, upper and lower limbs, frequency and duration etc.) have yet to be analyzed further. Furthermore, training status, specificity of muscle strength tests (dynamic versus isometric or isokinetic) and specificity of muscle mass assessments (locations of muscle hypertrophy assessments) seem to exhibit different effects on the results of the analysis. The role of these influencing factors, therefore, remains to be elucidated.